Recovery : the lost art of convalescence - Francis, Gavin (Penguin Life, 2023)
"Recovery offers tools and wisdom for convalescence, and shows how tending to our bodies, environments, and perspectives can help us move through the landscape of illness--and come out the other side whole"--